THE IMPACT OF COMPETENCE AND EMOTIONAL INTELLIGENCE ON THE PERFORMANCE OF RAUDHATUL ATHFAL TEACHERS IN SIMALUNGUN DISTRICT - Wahyudi, Muhammad; Ridwan, Rahmad (UIN Sumatera Utara Medan, 2023)
Based on the identification of several problems, namely: 1) there are still teachers who are not good at pedagogical competence, such as teachers who are still not good at designing daily learning program planning (RPPH), making learning media, 2) there are still teachers who are not good at emotional intelligence, such as teachers are not good at motivating themselves, that is they are still not good at using their deepest desire to move and guide towards the goals to be achieved, 3) there are still teachers who are not good at preparing lesson plans, implementing learning and evaluating learning which will affect teacher performance. From the identification of the problem, the formulation of the problem can be drawn, namely: 1) Does competence partially affect the performance of Raudhatul Athfal's teachers in Simalungun Regency?; 2) Does emotional intelligence partially affect the performance of teacher Raudhatul Athfal in Simalungun Regency; 3) Does competence and emotional intelligence simultaneously affect the performance of Raudhatul Athfal's teachers in Simalungun Regency? This research is quantitative with the help of the SPSS application. The method used in this study is a survey method with correlational analysis techniques. This study aims to analyze, test, and determine the effect of competency and emotional intelligence variables, partially and simultaneously on the performance of Raudhatul Athfal's teachers in Simalungun Regency. The results of the study show that competence has a partial effect on teacher performance. It can be seen from multiple linear regression analysis through the t-test that the competence variable has a Tcount of 4.893 while Ttable is 1.694 (Tcount 4.893 > Ttable 1.694) with a significant level of 0.000 <0.05, meaning that there is a significant influence between competence on teacher performance. There is a partial influence between Emotional Intelligence with a Tcount of 2.566 while Ttable is 1.694 (Tcount 2.566 > Ttable 1.665) with a significant level of 0.015 <0.05, meaning that there is a positive influence between Emotional Intelligence on teacher performance. There is a positive and simultaneous influence of Competency and Emotional Intelligence variables on Raudhatul Athfal's Teacher Performance in Simalungun Regency. With Fcount of 59.501 with a significant level of 0.000. (Fcount 59.501 > Ftable value 3.29 sig 0.000 <0.05).